Long-Term Grow-Out Affects Campylobacter jejuni Colonization Fitness in Coincidence With Altered Microbiota and Lipid Composition in the Cecum of Laying Hens - Asakura, Hiroshi; Nakayama, Tatsuya; Yamamoto, Shiori; Izawa, Kazuki; Kawase, Jun; Torii, Yasushi; Murakami, Satoshi (Frontiers in Veterinary Science, 2021)
Campylobacter jejuni is one of the leading causes of gastrointestinal illness worldwide and is mainly transmitted from chicken through the food chain. Previous studies have provided increasing evidence that this pathogen can colonize and replicate in broiler chicken during its breeding; however, its spatiotemporal kinetics in laying hen are poorly understood. Considering the possible interaction between C. jejuni and gut microbiota, the current study was conducted to address the spatiotemporal dynamics of C. jejuni in the cecum of laying hen over 40 weeks, with possible alteration of the gut microbiota and fatty acid components. Following oral infection with C. jejuni 81-176, inocula were stably recovered from ceca for up to 8 weeks post-infection (p.i.). From 16 weeks p.i., most birds became negative for C. jejuni and remained negative up to 40 weeks p.i.. 16S rRNA sequencing analyses revealed that most of the altered relative rRNA abundances occurred in the order Clostridiales, in which increased relative rRNA abundances were observed at >16 weeks p.i. in the families Clostridiaceae, Ruminococcaceae, Lachnospiraceae, and Peptococcaceae. Lipidome analyses revealed increased levels of sterols associated with bile acid metabolisms in the cecum at 16 and/or 24 weeks p.i. compared with those detected at 8 weeks p.i., suggesting that altered microbiota and bile acid metabolism might underlie the decreased colonization fitness of C. jejuni in the gut of laying hens.